منهج الشيخ محمد فضل الله السحيمي الأزهري (1964-1886م) واسهاماته في تدوين السيرة النبوية في أرخبيل الملايو - Nidzamuddin Zakaria
The research deals with the method of Sheikh Muhammad Fadlullah al-Suhaimi al-Azhari (1886-1964) and his contributions to codifying the Prophet’s biography in the Malay Archipelago through studying and analyzing his book “(Tarikh Islam Pada Menyatakan Perjalanan Sayyid al-Anam)” which was the first book in the Malay language that deals with all the events of the biography of The Prophet. he wrote it in 1918 in Indonesia to be a reference for all schools and religious institutes, as the study aims to track his contributions in the field of the prophetic biography and analyze his political, economic, social and religious ideas through his writings which amounted to 35 books and more than 145 articles published in Malay newspapers and magazines.besides, it traces the contributions of the Malay archipelago scholars to the biography of the Prophet until the al-Suhaimi period,and shows the development that he brought in writing the Prophet’s biography. as he made an important shift in the authorship movement in the field of prophetic biography by authoring the first book in the Malay language in Jawi script that includes all topics of the Prophet’s biography, according to a scientific method in which it relied on abbreviation and lack of redundancy, relying on a number of sources and references. it was sufficient to refer to it in the introduction to the book. The study used both the analytical, inductive, historical, and descriptive approach to study the subject. it comes out with a number of results, the most important of which are the following: al-Suhaimi puts in his book History of Islam, the emergence of the science of the jurisprudence of the prophetic biography in his era and was able to use the prophetic biography in the development of society by encouraging people follow the example of the Prophet’s approach, apply the Sunnah of the Prophet in their lives, move away from heresy and superstition, and respond to fatwas that contradict his opinion according to a scientific method, tragically to the Prophet’s approach to gradual advocacy and reform. Al-Suhaimi also contributed to supporting and encouraging women to seek knowledge inside and outside the country, along with his great role In developing education, establishing many schools and institutes and establishing scientific and political societies, which have contributed to the independence of Malaysia and Indonesia.